Correlation of CD4+ count and viral load with urinary tract infection and antimicrobial resistance pattern of bacterial uropathogens among HIV patients in Wolaita Sodo, South Ethiopia - Hantalo, Admasu Haile; Shano, Abera Kumalo; Meja, Tekilu Israel (Frontiers in Microbiology, 2024)
Background The permanence of HIV patients in healthcare provision centers exposes their weak immunity to various nosocomial microorganisms that migrate into and out of the hospital environment. The incidence of bacterial infections, including urinary tract infection, was inversely correlated with CD4+ T cells. Urinary tract infection (UTI) is one of the clinical problems among HIV patients. There was scarcity of published data on the relationship between viral load, CD4+ level, and UTI. This study aimed to assess the relationship between viral load and CD4 with bacterial UTI among HIV patients. Methods The cross-sectional study was conducted in the Wolaita Sodo Town Health Center ART clinic. The socio-demographic data were collected using a pre-designed questionnaire. Patients' charts were reviewed to collect the current CD4 and viral load. Urine specimens were inoculated on blood agar, cysteine lactose electrolyte deficient (CLED) agar, and MacConkey agar, and bacterial species were finally identified using various biochemical methods. Antimicrobial sensitivity testing was conducted using standard microbiological tests. Bivariate and multivariate analyses were employed to describe the association between pairs of variables and to examine the relationship between independent variables and dependent variables. Results In this study, the overall prevalence of urinary tract infection (UTI) was 13.7%. Escherichia coli, Staphylococcus aureus, Pseudomonas aeroginosa, Staphylococcus saprophyticus, Proteus mirabilis, and Klebsiella pneumoniae were bacterial uropathogens detected in this study. E.coli (45.7%) was the predominant isolate followed by S. aureus (14.3%). Positive correlation between CD4+ count and urinary tract infection was detected and found statistically significant (r = 0.288 p > 0.01), whereas the viral load and urinary tract infection negatively correlated and showed statistically significant association (p < 0.01). The resistance rate of E.coli was 94%, 75%, and 69% to ciprofloxacin, norfloxacin, and cefepime, respectively. This study revealed that E.coli exhibited 94% and 75% resistance to amoxicillin-clavulanic acid and tetracycline, respectively. K. pneumoniae demonstrated complete resistance (100%) to amoxicillin-clavulanic acid, tetracycline, and trimethoprim-sulfamethoxazole, while showing 100% susceptibility to ciprofloxacin and nitrofurantoin. In the present study, the magnitude of the multi-drug resistance (MDR) was found to be 80%. CD4+ count, combination of antiretroviral therapy (ART) drugs, and a history of hospitalization were risk factors for urinary tract infection. Conclusion In the current study, urinary tract infection emerged as a significant health concern among people living with HIV following their ART. The occurrence of urinary tract infection among HIV patients could be influenced by multifactorial factors that require further study. The CD4+ count was positively correlated with the prevalence of UTI, whereas the viral load was negatively correlated. The CD4+ count, combination of ART, and history of hospitalization were independent risk factors for UTI. The prevalence of MDR bacterial pathogens were notably high. Therefore, the treatment of UTI in HIV patients should be prescribed based on antibacterial susceptibility testing results.